Analysis of Shielded Metal Arc Welding (SMAW) on high manganese steel hammer-mill crusher / Yusup Hendronursito...[et al.] - Hendronursito, Yusup; Isnugroho, Kusno; David, Candra Birawidha; Amin, Muhammad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Hammer-mill crusher is the main component of crushing machine, used to crush the material into smaller size. In this study the crusher was produced by casting in an induction furnace, which composition consisted of 1.64% C, 8.77% Mn, 2.56% Cr, and 3.75% Cu. Unfortunately, the production process frequently yielded undesirable defects such as blowhole, gas porosity and smooth - walled cavities, and the welding process was required to repair such defects. This study aimed to determine the welding parameters for hammer-mill crusher welding with Shielded Metal Arc welding (SMAW) process that covered the effect of welding current of 90A, 120A, 150A, welding speed of 0.8 mm/s, 1 mm/s, 1.7 mm/s and filler metal of AWS A5.5 (E7016) and AWS A5.13 (E7-UM-300K). The qualification standard for welding refered to The American Society of Mechanical Engineers (ASME) Section IX Welding and Brazing Qualification. The testing refered to ASME IX QW - 140 (purpose of the testing and inspection of welds) for tention test (QW-141.1) and visual examination (QW-144), ASME IX QW - 190 (other tests and examination) for Radiographic examination (QW - 191). The hardness test was performed to determine whether the hardness of weld pool is the same or close to the value of the hammer-mill crusher hardness. This parameter was important considering the function of hammer-mill as hard material crusher. The results showed that the optimum welding condition are: welding speed of 1 mm/ s, welding current 120A and filler metal AWS A5.13 (E7-UM-300K). The best results of mechanical properties include hardness 254 HV, elasticity modulus 277.261 MPa, and tensile strength283.605 Mpa.